Drug Market Criminology: Combining Economic and Criminological Research on Illicit Drug Markets. (September 2018) - Moeller, Kim
There is a divide between economic and criminological research on illicit drug markets. Economists have focused on modeling markets at an abstract level, while criminologists have focused on offending in individual street-level marketplaces. This article combines the economic and criminological research on illicit drug markets through the lens of social embeddedness theory. The analysis concerns how participants reduce the uncertainties that follow from the illegality of the product, the lack of reliable information on product quality, and the trustworthiness of the trading partner. Social embeddedness theory is reconcilable with transaction cost economics but puts more emphasis on the importance of longer term interpersonal relations and trust. Using this framework provides a middle-range interpretation for the economic irregularities observed in drug markets: how prices deviate from the competitive equilibrium and how distributors develop and maintain interpersonal trust and balance competitiveness with security concerns.